New spring : the novel - Jordan, Robert, 1948-2007 (Jordan, Robert, 1948-2007. Wheel of time, 2020)
For three days battle has raged in the snow around the great city of Tar Valon. In the city, a Foretelling of the future is uttered. On the slopes of Dragonmount, the immense mountain that looms over the city, is born an infant prophesied to change the world. That child must be found before the forces of the Shadow have an opportunity to kill him. Moiraine Damodred, a young Accepted soon to be raised to Aes Sedai, and Lan Mandragoran, a soldier fighting in the battle, are set on paths that will bind their lives together. But those paths are filled with complications and dangers, for Moiraine, of the royal House of Cairhien, whose king has just died, and Lan, considered the uncrowned king of a nation long dead, find their lives threatened by the plots of those seeking power. "New Spring," the novella first published in Legends, related some of these events, in compressed form: New Spring: The Novel tells the whole story.